Tradisi Islam, Tradisi Arab dan Tradisi Jawa: Membaca Karya dan Pemikiran K.H. Ahmad ar-Rifai Kalisalak - Agus Iswanto (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2017)
This article reviews the book of philological research on one of the works of a Javanese ulama, namely K.H. Ahmad ar-Rifai Kalisalak. The work is entitled nazam Tarekat. Aside from being a philological research, which aims to present the text edition of the manuscript of ar-Rifai, this book also examines the context surrounding the author's life and the social function of the text. This book is an example for the research that combines the study of philology and Islamic studies in a research project. This book emphasizes the rich intellectual traditions of the author, Ahmad ar-Rifai, which includes Islamic traditions, Arabic poetry and Javanese poetry. These three traditions, in Gadamer hermeneutic terms, merge to produce a work of the nazam Tarekat. The work of this book can also be an important proof of the contextualization strategy of Islamic preacing in Muslim Nusantara society.Keywords: philology, Indonesian Islamic intellectual tradition, hermeneutic, Ahmad ar-Rifai Artikel ini mengulas buku yang berupa hasil penelitian filologis tentang salah satu karya dari seorang ulama Jawa, yakni K.H. Ahmad ar-Rifai Kalisalak. Karya tersebut berjudul nazam Tarekat. Selain sebagai sebuah penelitian filologis, yang tujuannya menyajikan edisi teks dari naskah karya ar-Rifai, buku ini juga mengulas konteks yang melingkupi kehidupan sang pengarang dan fungsi sosial dari teks yang dikaji. Buku ini menjadi contoh untuk hasil penelitian yang memadukan kajian filologis dan kajian Islam dalam satu proyek penelitian. Buku ini menegaskan tentang kekayaan tradisi intelektual yang dimiliki sang pengarang, Ahmad ar-Rifai, yang meliputi tradisi Islam, tradisi puisi Arab dan puisi Jawa. Ketiga tradisi tersebut, dalam istilah hermeneutik Gadamer, melebur sehingga menghasilkan sebuah karya nazam Tarekat. Karya Buku ini juga dapat menjadi bukti penting tentang strategi kontekstualisasi ajaran Islam dalam masyarakat Muslim Nusantara.Kata kunci: filologi, tradisi intelektual Islam Indonesia, hermeneutik, Ahmad ar-Rifai